2017
DOI: 10.3389/fmars.2017.00413
|View full text |Cite
|
Sign up to set email alerts
|

Projecting Marine Mammal Distribution in a Changing Climate

Abstract: Climate-related shifts in marine mammal range and distribution have been observed in some populations; however, the nature and magnitude of future responses are uncertain in novel environments projected under climate change. This poses a challenge for agencies charged with management and conservation of these species. Specialized diets, restricted ranges, or reliance on specific substrates or sites (e.g., for pupping) make many marine mammal populations particularly vulnerable to climate change. High-latitude,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 116 publications
2
78
0
Order By: Relevance
“…Our results suggest that the forecasted sea ice changes (Böning, Dispert, Visbeck, Rintoul, & Schwarzkopf, 2008;Rignot et al, 2008;Silber et al, 2017) have the potential of heavily impacting AMWs. The nature and magnitude of future responses of AMWs as a species are uncertain in novel environments as projected under climate change.…”
Section: Con Clus Ionmentioning
confidence: 76%
See 2 more Smart Citations
“…Our results suggest that the forecasted sea ice changes (Böning, Dispert, Visbeck, Rintoul, & Schwarzkopf, 2008;Rignot et al, 2008;Silber et al, 2017) have the potential of heavily impacting AMWs. The nature and magnitude of future responses of AMWs as a species are uncertain in novel environments as projected under climate change.…”
Section: Con Clus Ionmentioning
confidence: 76%
“…Moreover, biases in shipboard cetacean surveys in ice-covered waters may arise from the influence of the ship's presence (e.g., its noise and the noise caused by ice-breaking activities) on the detection rate of cetaceans due to behavioral reactions (Erbe & Farmer, 2000). This information, however, is crucial for assessing the species' vulnerability with regard to predicted, climate-related changes in sea ice conditions (Silber et al, 2017). This information, however, is crucial for assessing the species' vulnerability with regard to predicted, climate-related changes in sea ice conditions (Silber et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Distribution shifts are considered the most likely response of large mobile cetaceans to climate change (Silber et al, ; Sydeman et al, ). History has shown that humpback whale distribution can change on the scale of a few decades, particularly in cases of overexploitation and local extirpation.…”
Section: Discussionmentioning
confidence: 99%
“…Sympatric species may respond differently to environmental change and anthropogenic pressures, making the identification of species-specific habitat use patterns a key requirement for effective conservation (Schaefer, Jetz, & Böhning-Gaese, 2008;Silber et al, 2017). Sympatric species may respond differently to environmental change and anthropogenic pressures, making the identification of species-specific habitat use patterns a key requirement for effective conservation (Schaefer, Jetz, & Böhning-Gaese, 2008;Silber et al, 2017).…”
Section: Introductionmentioning
confidence: 99%